2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29115
|View full text |Cite
|
Sign up to set email alerts
|

What Does Career and Personal Success Look Like? Engineering Students' Projections for Post-Graduation Plans

Abstract: He teaches human-centered engineering design, design thinking, and design innovation project courses. Dr. Lande researches how technical and non-technical people learn and apply a design process to their work. He is interested in the intersection of designerly epistemic identities and vocational pathways. Dr. Lande is the PI/co-PI on NSF-funded projects focused on engineering doing and making, citizen science and engineering outreach, and "revolutionizing" engineering education. He has also been an instructor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A fourth study, conducted at Arizona State University, focused on a single technique from DYL, the "odyssey plan," in which students map out multiple ways in which their life could unfold. The study's results suggested that in using the odyssey plan, by both first-year and fourth-year students, the students generally chose to be contributing members of society, recognized a need for experience, and referenced having a family or loved ones as an important aspect of success [10]. Again, though, neither of these studies reported whether DYL led to actual changes in (or confirmation of) students' specific career plans.…”
Section: Introductionmentioning
confidence: 90%
“…A fourth study, conducted at Arizona State University, focused on a single technique from DYL, the "odyssey plan," in which students map out multiple ways in which their life could unfold. The study's results suggested that in using the odyssey plan, by both first-year and fourth-year students, the students generally chose to be contributing members of society, recognized a need for experience, and referenced having a family or loved ones as an important aspect of success [10]. Again, though, neither of these studies reported whether DYL led to actual changes in (or confirmation of) students' specific career plans.…”
Section: Introductionmentioning
confidence: 90%